Medicinal Plant Images - Cock, I.E. (Pharmacognosy Communications)
Kigelia africana(commonly known as sausage tree). Multiple parts of the K. africana tree have been used in traditional healing systems in the treatment of a variety of medical conditions and complaints. The powdered mature fruit is used to treat wounds, abscesses, and ulcers, whilst the green fruit is used to treat syphilis and rheumatism.1-3 An infusion made from the ground bark and fruit is used to treat stomach problems in children.1,3 Roots and bark are used to treat pneumonia.1 In West Africa, leaves and twigs are used to treat wounds, dysentery, stomach and kidney disorders, snakebite, and rheumatism.4 The fruit is used to treat constipation, gynaecological disorders, haemorrhoids, lumbago and dysentery.4 Slices of mature baked fruits are used to ferment and flavour traditional African beer.5 Extracts prepared from the bark have cytotoxic activities and have shown promising results in treating melanoma and renal carcinoma.6 Bark and root solvent extracts have been reported to inhibit the growth of Escherichia coli, Enterobacter aerogens, Klebsiellapneumoniae, Salmonella typhi, Proteus vulgaris, Pseudomonas aeruginosa, Staphylococcus aureus and Bacillus cereus.7 In a similar study, solvent extracts prepared from stem and root bark have also been shown to inhibit growth of E. coli, P. aeruginosa, S.aureus and Candida albicans. 8,9 Other studies have also reported antibacterial activity for K. africana leaf10,11 extracts of particular interest, polar K. africana leaf extracts have been shown to inhibit the growth of the bacterial trigger of rheumatoid arthritis.10 Extracts prepared from the K. africana fruit inhibited the growth of a panel of Gram positive and Gram negative bacteria.11,12 Furthermore, extracts from various parts of the K. africana plant have been shown to have high antioxidant contents,13,14 further indicating the therapeutic potential of this species.This photograph was taken Windhoek Botanical Gardens, Namibia in 2012 by Dr Ian Cock.